Global Economic Prospects and the Developing Countries 2003 : Investing to Unlock Global Opportunities - World Bank (Washington, DC, 2013)
Strong cyclical dynamics, together with an easing of macroeconomic policies in the United States and elsewhere, have boosted large parts of the global economy, into the initial phase of a recovery in 2002. Nonetheless, the global recovery is fragile, because investment spending is insufficient to underpin continuing growth, although long-term prospects remain promising. Although global competition is creating new opportunities for developing countries, harnessing globalization requires reducing barriers to competition, using targeted interventions carefully, but essentially, supported by sound public investments. International agreements on investment, and competition policies can provide benefits through reciprocity, while agreements on investment policy are likely to have strong development effects, only if they deal with the big issues facing developing countries. Consequently, competition agreements should focus on restraints to competition that hurt developing countries: policy barriers in markets abroad; private restraints on competition; and, trade restraints officially sanctioned.